Golgi-associated phosphohydrolases in Trypanosoma brucei brucei - Grab, D.J.; Webster, P.; Verjee, Y.; Lonsdale-Eccles, J. (Elsevier, 1997)
Various parasitic protozoa of the family Trypanosomatidae such as Crithidia spp. [1]; Trypanosoma cruzi [2]; Leishmania donovani [3] and salivarian trypanosomes [4-8] have been shown to contain acid phosphatase activity (EC.3.1.3.2, orthophosphoric-monoester phosphohydrolase activity). Acid phosphatase activity was first localized by histochemical electron microscopic techniques to the flagella pocket, tubules, vesicles and trans-Golgi in Trypanosoma brucei [4], although subsequent studies suggested that acid phosphatase activity may also be found on the cell surface of T. b rhodesiense [5] and T. congolense [8]. Somewhat surprisingly, these and other biochemical subfractionation studies [9,10] showed that the level of acid phosphatase activity within the lysosomes to T. brucei was relatively low. The highest level of acid phosphatase activity was found within a Golgi membrane-containing fraction that had been purified by sucrose-density gradient [11,12]. Both tartrate-sensitive and tartrate-resistant acid phosphatase were distributed between the flagella pocket and the surface membrane of T. rhodesiense. Schell et al. [6] purified a 70 KD tartrate-sensitive acid phosphatase from T. brucei and also showed that approximately 50 percent of both the tartrate-sensitive and the tartrate-resistant enzymes may be located together at the cell surface. Unfortunately, using the fractionation techniques then available, it was not possible to distinguish the distribution of these enzymes within the flagella pocket or other organelle sub-compartments. It have been biochemically and morphologically characterized subcellular membrane fractions of T. brucei (obtained from Percoll and/or sucrose gradients) and shown that the Golgi membranes contain the highest specific activity levels of acid phosphatase [9]. Although some of this enzyme activity mat also be found on purified lysosomes and flagella pocket membranes, the levels in these compartments are considerably lower [9,10]. the effect of tartrate on acid phosphatase activity in these organelles, relative to the homogenate control is shown. In the experiment, a Golgi fraction had an 18-fold increase in specific activity over the initial homogenate, and this activity was inhibited over 90 percent by tartrate. In comparison, flagellar pocket and lysosomes expressed only 0.5 and 2.5 times the homogenate value respectively. These activities were also inhibited by tartrate. Using the powerful technique preparative free-flow electrophoresis [29] which has been used to T. brucei [13] it is showed that Golgi-associated tartrate-sensitive acid phosphatase is located in a sub-component of the Golgi fraction of T. brucei lysates. Using free flow electrophoresis, and galactosyltransferase (GTase) as a marker for Golgi membranes (9,11), it was possible to separate classifically prepared Golgi fractions into at least five major and several minor Golgi membrane, galactosyltransferase-containing, fractions.